Discovery science 14th international conference, DS 2011, Espoo, Finland, October 5-7, 2011. proceedings - International conference on discovery science 2011 Espoo, Finland); Elomaa, Tapio 1963-.; Hollmén, Jaakko; Mannila, Heikki; SpringerLink (Online service). (Berlin, Heidelberg Springer, 2011)
This book constitutes the refereed proceedings of the 14th International Conference on Discovery Science, DS 2011, held in Espoo, Finland, in October 2011 - co-located with ALT 2011, the 22nd International Conference on Algorithmic Learning Theory. The 24 revised full papers presented together with 5 invited lectures were carefully revised and selected from 56 submissions. The papers cover a wide range including the development and analysis of methods for automatic scientific knowledge discovery, machine learning, intelligent data analysis, theory of learning, as well as their application to knowledge discovery.
Electronic reproduction.
Keywords: Science -- Philosophy -- Congresses; Discoveries in science -- Congresses; Data mining -- Congresses; Research -- Data processing -- Congresses; Electronic books